Rancang Bangun Sistem Proteksi Dan Monitoring Kebocoran Gas Hidrokarbon Berbasis Fuzzy Sugeno - Oktavianto, Rinaldi; Wardhana, Asepta Surya; Sahrin, Alfin (Program Studi Teknik Elektro Universitas Khairun, 2022)
One of the risks in the oil industry is leakage of gases that are toxic or flammable. Fire and Gas System (FGS) used to detect the release of hazardous gases then carry out mitigation actions which can be alarms, indicators, or shutdown systems. This study aims to make a simple prototype of Fire and Gas System in the manifold area with three pipelines (Line-A, Line-B, and Line-C). The output of the system includes indicator, alarm, and shutdown system (closing gas flow and activate the exhaust fan). The system is integrated with Delphi and Arduino. The decision making based on Sugeno fuzzy. Based on the results, it was found that the suitability of fuzzy system reached 100%. The monitoring is displayed in graphical form. While the system response is appropriate, but there is a delay of about 1.5 seconds. Protection system is able to normalize conditions in about 77.5 seconds.